The Empirical Evidences of Physical Store Survival of Hijab Fashion Industry in Digital Era - Diantika, Mei Rizki; Hartati, Sri (Journal of Innovation, Business and Entrepreneurship, 2019)
The trend of wearing hijab in Indonesia is booming today. But, Nowadays several fashion business which has physical store that had exist suddenly closed down, they can not survive because they cannot knowing their customer need, technology make a system changes.This research aims to recognize and understand how physical store survive in digital era especially in hijab company and develop strategy of Khalisa Hijab which is startup hijab in Bandung. This research using qualitative approach with in-depth interview. It has interviewed five informants from different hijab companies which have more than three physical store. The researcher focused on the strategic retail model that owned by those companies. To recognize and understand the strategic retail model in hijab companies, there are four elements that the researcher used. The elements is product, service, positioning, and technology which is adopted from Gustafsson and Gustavsson (2013). Based on the result, to be different and unique product, the hijab company can make design product which has ethnic style from Indonesian culture or the raw material should up to date such as using laser cut and hijab printing. The store environment should show the value of brand. Each hijab company should focus on their customer want and customer buying behavior and agile with the existing changes. Based on the result of the research, there are develop strategy that can be implemented in Khalisa Hijab. Khalisa Hijab should engages its customer with brand via website or social media. The brand of Khalisa Hijab should be known by society especially in Bandung. Then, it should produce authentic product that can be the identity of Khalisa Hijab.And maintain and manage the customers with discount and member card that always broadcast the customer via Instagram feed and stories for gaining loyal customer.Keywords: Digital Technology, Hijab Company, Physical Store, The Strategic Retail Model